Doubling recruitment of pediatric low-grade Glioma within two decades does not change outcome: report from the german LGG studies = Verdopplung der Rekrutierungszahl niedrig-gradiger Gliome des Kindes- und Jugendalters innerhalb von 20 Jahren ändert die Überlebenschancen nicht - Gnekow, Astrid K.; Kandels, Daniela; Pietsch, Torsten; Bison, Brigitte; Warmuth-Metz, Monika; Thomale, Ulrich W.; Kortmann, Rolf-D.; Timmermann, Beate; Driever, Pablo Hernàiz; Witt, Olaf; Schmidt, René; Spix, Claudia (Klinische Pädiatrie, 2021)
Successive multicenter studies for pediatric low-grade glioma (LGG) in Germany were accompanied by a doubling of annual recruitment over 2 decades. We investigated whether this increase conveyed a change of epidemiologic characteristics or survival. Methods and results. Participating centers reported 4634 patients with the radiologic/histologic diagnosis of LGG (1996-2018), rising from 109 to 278/year. Relating these numbers to all pediatric CNS tumors registered at the German Childhood Cancer Registry, the LGG fraction and annual crude incidence rates increased (32% to 51%; 0.94 to 2.12/100,000 children/adolescents<15 years). The consecutive LGG studies recruited 899 (HIT-LGG 1996), 1592 (SIOP-LGG 2004), and 1836 (LGG-registry) patients with similar distribution of tumor-sites, histology, and dissemination. 5-year overall survival was 96%-98% at median observation time of 8.1 years. Acknowledging unequal follow-up periods, 589/899 (66%), 1089/1582 (69%), and 1387/1836 (76%) patients remained under observation, while 1252/4317 received adjuvant treatment with decreasing frequency of front-line radiotherapy from 16% to 5%. Conclusion Pediatric LGG incidence rates in Germany are now comparable to other European countries. The rise in patient numbers followed implementation of standard-of-care treatment protocols, but did not result in relevant changes of epidemiologic or clinical parameters or survival. Shifts in patient distribution between treatment arms reflect growing acceptance of the LGG therapy algorithm. Hintergrund In den vergangenen 20 Jahren hat sich die jährliche Patientenrekrutierung in den aufeinanderfolgenden multizentrischen Studien für pädiatrische niedrig-gradige Gliome (LGG) in Deutschland verdoppelt. Wir haben untersucht, ob sich mit dieser Zunahme auch epidemiologische Merkmale oder das Überleben verändert haben. Methodik und Ergebnisse Zwischen 1996 und 2018 meldeten die teilnehmenden Zentren insgesamt 4634 Patienten mit der radiologischen/histologischen Diagnose eines LGG. Die Zahl stieg von anfangs 109 bis 278 Patienten pro Jahr. Gleichzeitig stieg der Anteil der LGGs an allen am Deutschen Kinderkrebsregister gemeldeten pädiatrischen Hirntumoren von 32 auf 51%, die jährliche Inzidenz erhöhte sich von 0,94 auf 2,12/100 000 Kinder/Jugendliche<15 Jahre. Die aufeinanderfolgenden LGG-Studien rekrutierten 899 (HIT-LGG 1996), 1592 (SIOP-LGG 2004) und 1836 (LGG-Register) Patienten mit vergleichbarer Verteilung von Tumorsitz, Histologie und Disseminierung. Das 5-Jahres-Überleben lag bei einer medianen Nachbeobachtungszeit von 8,1 Jahren zwischen 96 und 98%. Unter Berücksichtigung der ungleich langen Follow-up-Zeit wurden 589/899 (65,5%), 1089/1582 (68,8%) und 1387/1836 (75,5%) Patienten bislang beobachtet, während 1252/4317 eine adjuvante Therapie erhielten. Dabei sank der Anteil der primären Radiotherapie von 16 auf 5%. Schlussfolgerung: Die Rekrutierung pädiatrischer LGG ist dank Implementierung verbindlicher Therapiestandards in Deutschland gestiegen, ohne zu relevanten Veränderungen epidemiologischer oder klinischer Merkmale oder des Überlebens zu führen. Die Inzidenz ist mit anderen europäischen Ländern vergleichbar. Verschiebungen der Patientenzuteilung zwischen den Therapiearmen spiegeln die zunehmende Akzeptanz des LGG-Therapie-Algorithmus wider.